Disordered mechanical metamaterials - Zaiser, Michael; Zapperi, Stefano (Nature Reviews Physics, 2023)
Mechanical metamaterials are a class of artificial materials whose geometry is engineered to have peculiar mechanical properties or programmed responses that are difficult to find in conventional materials. Typically, metamaterials are periodic, but incorporating disorder into their design can provide improved functionalities over ordered structures. In this Perspective article, we use examples of biological materials with disordered structures to elucidate how disorder can enhance the mechanical performance of engineered mechanical metamaterials. We clarify opportunities and pitfalls posed by randomness, highlight the increasingly prominent role played by disorder in novel design strategies for mechanical metamaterials and discuss recently developed algorithmic and data-driven strategies for the design of disordered optimized metamaterials.
Created from Fastlane, Scopus look-up